Motor excitability during movement preparation in Tourette syndrome. Issue 1 (28th November 2013) - Draper, Amelia; Jude, Lucinda; Jackson, Georgina M.; Jackson, Stephen R.
<x xml:space="preserve">Abstract</x> Tourette syndrome (TS) is a neurodevelopmental disorder characterized by the occurrence of motor and vocal tics. TS has been linked to the impaired operation of cortical‐striatal‐thalamic‐cortical circuits that give rise to hyper‐excitability of cortical motor areas, which may be exacerbated by dysfunctional intra‐cortical inhibitory mechanisms. That said, many individuals gain control over their tics during adolescence and it has been suggested that this increased control arises as a result of the development of mechanisms that operate to suppress corticospinal excitability (CSE) ahead of volitional movements. Here we used single‐pulse transcranial magnetic stimulation (TMS) in conjunction with a manual Go/NoGo task to investigate alterations in CSE ahead of volitional movements in a group of adolescents with TS (N = 10). Our study demonstrated that CSE, as measured by TMS‐induced motor‐evoked potentials (MEPs), was significantly reduced in the TS group in the period immediately preceding a finger movement. More specifically, we show that individuals with TS, unlike their age‐matched controls, do not exhibit the predicted increase in mean MEP amplitude and decrease in MEP variability that immediately precede the execution of volitional movements in typically developing young adults. Finally, we report that the magnitude of the rise in MEP amplitude across the movement preparation period in TS is significantly negatively correlated with clinical measures of motor tic severity, suggesting that individuals with severe motor tics are least able to modulate motor cortical excitability.